EO.0.0.7943 - Couttenier, Maarten (BMGN - Low Countries Historical Review, 2018)
By examining one ‘ethnographic’ object kept at the Royal Museum for Central Africa, this article discusses three consecutive demands for restitution of eo.0.0.7943, in 1878, in the 1960s-1970s, and in 2016. Neither informal nor official demands resulted in the actual return of the object to Congo. Instead, it featured in major exhibitions in Belgium, the Netherlands and the United States. While the Tervuren museum ‘donated’ other objects to local Congolese museums in the 1970s and 1980s, Congolese voices by now seem powerless, and debate is almost inexistent in Belgium. So what can museums and communities do? I argue that both provenance research and local expertise can provide rich and useful contemporary insights on objects and people, as well as on acquisition and exhibition history. Such objects and insights may be integrated in exhibitions Europe and Africa, with all its uplifting and darker consequences. What is more valuable: owning an object or the encounter?This article is part of the forum 'Decolonisation and colonial collections: An unresolved conflict'Door te kijken naar één ‘etnografisch’ object, bewaard in het Koninklijk Museum voor Midden-Afrika, bespreekt dit artikel drie opeenvolgende vragen naar restitutie van eo.0.0.7943, in 1878, de jaren 1960-1970 en in 2016. Informele, noch officiële vragen hebben echter geresulteerd in de terugkeer van het object naar Congo. Het werd daarentegen wel getoond op grote tentoonstellingen in België, Nederland en de Verenigde Staten. Het museum in Tervuren ‘schonk’ wel degelijk andere objecten aan lokale Congolese musea in de jaren 1970 en 1980, maar vandaag lijken Congolese stemmen machteloos en het debat is bijna onbestaande in België. Dus wat kunnen museums en gemeenschappen doen? Mijn inziens kunnen oorsprongsonderzoek en lokale expertise rijke en bruikbare hedendaagse inzichten opleveren over objecten en mensen, en de geschiedenis van verzamelen en tentoonstellen. Objecten en inzichten die kunnen worden geïntegreerd in tentoonstellingen in Europa en Afrika met al zijn verheffende en meer duistere gevolgen. Wat is waardevoller: een object bezitten of de ontmoetingDit artikel is onderdeel van het forum 'Decolonisation and colonial collections: An unresolved conflict'